2020
DOI: 10.1158/1535-7163.mct-20-0249
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Predictive Biomarkers in Patients with Metastatic Colorectal Cancer Receiving Regorafenib

Abstract: ◥Regorafenib is a tyrosine kinase inhibitor approved by the FDA for the treatment of patients with chemotherapy refractory metastatic colorectal cancer (mCRC). Regorafenib inhibits signaling through multiple receptors associated with angiogenesis, metastasis, and tumor immunity. Here, we report biomarker results from LCCC1029, a randomized, placebo-controlled, phase II trial of chemotherapy AE regorafenib in patients with second-line mCRC. A panel of 20 soluble protein biomarkers (termed the Angiome) was asses… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Small studies suggest that APC mutations or FGFR1 amplification in tumor tissue were more enriched in REG patients with a clinical benefit than those without, ( 28 ) and plasma VCAM-1 was potentially predictive of OS benefit in REG treatment. ( 29 ) A survival benefit of FTD/TPI was observed regardless of KRAS status. ( 11 , 12 ) High thymidine kinase 1 (TK1) expression level correlated with a larger survival benefit in FTD/TPI treatment, ( 30 ) although no significant difference in TKI expression according to PTL was reported.…”
Section: Discussionmentioning
confidence: 99%
“…Small studies suggest that APC mutations or FGFR1 amplification in tumor tissue were more enriched in REG patients with a clinical benefit than those without, ( 28 ) and plasma VCAM-1 was potentially predictive of OS benefit in REG treatment. ( 29 ) A survival benefit of FTD/TPI was observed regardless of KRAS status. ( 11 , 12 ) High thymidine kinase 1 (TK1) expression level correlated with a larger survival benefit in FTD/TPI treatment, ( 30 ) although no significant difference in TKI expression according to PTL was reported.…”
Section: Discussionmentioning
confidence: 99%
“…To enrich patients most likely to benefit, as well as to investigate the molecular impact of the drug, blood-based biomarkers were analyzed using multiplex ELISA to quantitatively assess circulating proteins related to angiogenesis, inflammation and immunity. This panel, termed the angiome [ 52 ], is a protein multiplex array that was consistently applied to several TRC105 clinical trials in order to explore potential prognostic, predictive and pharmacodynamic biomarkers. A list of all the clinical trials testing TRC105 is shown in Table 1 .…”
Section: Trc105 Clinical Trialsmentioning
confidence: 99%
“…Patients who progressed at or before cycle 3 had only two collections. Angiokines were measured as previously described and validated (14,15). All samples underwent one freeze-thaw cycle prior to analysis.…”
Section: Plasma Angiokine Analysismentioning
confidence: 99%